Thyroid activity and human physical and mental health: environmental and clinical aspects - V. L. Romaniuk; O. G. Rud; L. P. Goralskyi; O. O. Kyrylchuk; B. V. Gutyj (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
Based on the results of theoretical and practical research, the article defines the ecological and clinical aspects of human physical and mental health in connection with the activity of the thyroid gland in normal and pathological conditions. In general, quantitative and qualitative indicators of health as a bio-psycho-social and morpho-functional phenomenon are closely related to humoral and nervous mechanisms of regulation, as well as the body's reactivity, taking into account age and gender characteristics. Special attention should be paid to studies on the influence of thyroid activity on the formation of group reactivity (constitution), as well as nonspecific reactivity, including stress as a general adaptation syndrome. At the same time, the conditions of potential and real biological and military threats, as well as various forms of human activity, including the educational process, are accompanied by physiological and psychological stress, which requires appropriate interdisciplinary research on human stress resistance as a significant component of physical and mental health. In this regard, during the training, methods for diagnosing the body's stress resistance were tested according to certain morphological indicators and indices, taking into account the activity of the thyroid gland and its functional influence on the formation of the human constitution. In addition, taking into account environmental and social conditions, the potential levels of interdisciplinary research on the comprehensive assessment of human physical and mental health indicators are identified.